IoT Web-Based Student Curfew Management System - MOHD SHAH, UMAIRAH; Nayef Abdulwahab Mohammed Alduais (Applied Information Technology And Computer Science, 2026)
This project was developed to address inefficiencies and limitations associated with manual curfew enforcement at Universiti Tun Hussein Onn Malaysia (UTHM). Utilizing Radio Frequency Identification (RFID), PHP, ThingSpeak and MySQL, the system automates student entry and exit logging, real-time monitoring, violation tracking, and permit management. The development followed a structured parallel methodology, enabling concurrent progress on essential modules such as login authentication, profile management, RFID integration, and notification systems. The implemented system demonstrated significant improvements, including enhanced data accuracy, streamlined administrative processes, and real-time reporting capabilities. Feedback from initial user testing indicated positive reception regarding usability and operational efficiency. Despite these successes, limitations such as scalability concerns and the potential need for enhanced data security measures remain. Future work involves addressing these issues through optimization of database management and implementing advanced cybersecurity measures, ensuring high performance even under increased user load and data volume.